Intellectual Capital and Performance of Staff at Selected Institutions of Higher Learning in Uganda - Emmanuel, Sempijja; Madinah, Nabukeera; Musa, Matovu (Journal of Education and Practice, 2024)
Purpose: The study examined the relationship between intellectual capital and performance of staff at selected institutions in Uganda. The specific objectives were; i) To establish the relationship between human capital and performance of staff at selected institutions of higher learning in Uganda; ii) To establish the relationship between relational capital and performance of staff in selected institutions of higher learning in Uganda and iii) To establish the relationship between structural capital and performance of staff in selected institutions of higher learning in Uganda. Methodology: A cross-sectional design was used alongside a quantitative approach whereby a questionnaire was employed to collect the data from the 103 respondents who included lecturers from 10 selected institutions of higher learning. The results were computed using multiple regression and correlation analysis using SPSS and upon analysis, Findings: The outcomes exposed that; a) human capital has a positive but significant relationship with performance of staff at selected institutions of higher learning in Uganda (r = .536**, p<0.0001); b) there is a moderate relationship between relational capital and performance of staff at selected institutions of higher learning in Uganda (r = .374**, p>0.0001); c) there is a positive and very significant relationship between structural capital and performance of staff at selected institutions of higher learning in Uganda (r = .586**, p<0.0001). Unique Contribution to Theory, Policy and Practice: The research outcome undertakes that private institutions do not give attention to developing relational capital although it’s a very important aspect. It is also imperative to note that more resources are invested in the structural capital given its serious and observable impact on performance if it is put to utmost utilization. The study empirically differentiates the impacts of human, relational and structural capital on staff performance in institutions of higher learning offering context-specific insights and practically underscores the investment in structural and relational capital and continuous human capital development guiding resource allocation and policy formulation to enhance staff performance in Uganda.